Intrasellar Parasitic Infection: Finding the Culprit - How to Get the Right Diagnosis - Buravej Assavapongpaiboon; Behrouz Salehian (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2017)
Purpose: Parasitic diseases can involve central nervous system presenting with various manifestation. However, parasitic infection of pituitary is very rare, unexpected and can be missed diagnosis with tumor. Organisms, clinical features and diagnostic method of parasitic infection in sella turcica were described in this review. Methods: Case reports or case series from MEDLINE, PubMed, and Scopus updated to June 2016 were searched. Only full text papers from original publication which allows data abstraction on clinical, laboratory and neuroimaging fi ndings of intrasellar parasitic infection were included. Results: Out of 28 adult patients and 6 children, neurocysticercosis, toxoplasmosis, malaria, hydatid disease and amebiasis have been reported with pituitary involvement. All pediatric cases were involved in congenital toxoplasmosis. For adults, the two most frequent symptoms were headache (86%) and visual symptoms (61%). Sixty-eight percent of adults had hormonal disturbance which panhypopituitarism and hyperprolactinemia were most common. The majority of the cases had a defi nitive diagnosis of infection from indentifying parasitic organism from pathology except all cases of congenital toxoplasmosis, malaria and 4 cases of cysticercosis which diagnosis was established on the basis of neuroimaging fi ndings and immune diagnosis tests. Conclusions: History of risk for exposure and clinical manifestations of headache, visual disturbance,endocrine disturbance and eosinophilia are initial clues that lead to diagnosis of parasitic pituitary infection. In addition, hormonal dysfunction should be carefully evaluated. Defi nite diagnosis requiring parasitic identifi cation is occasionally invasive. Immunodiagnosis or molecular diagnosis with neuroimaging can be applied to achieve the correct diagnosis.